PENGARUH IOS, LEVERAGE DAN PROFITABILITAS PADA KEBIJAKAN DIVIDEN DENGAN NILAI PERUSAHAAN SEBAGAI VARIABEL MODERATING - Sari, Ayu Etika; Muliartha RM, Ketut (E-Jurnal Akuntansi, 2017)
The purpose of the study is to examine the role of the company's value as a moderating variable relationship between IOS, leverage and profitability in the dividend policy. The study was conducted during the period 2013 - 2015 in the Indonesian stock exchange at a total of 143 manufacturing companies with purposive sampling and 17 sample observations with moderation as regression analysis techniques. The analysis showed IOS negative effect on dividend policy, leverage negative effect on dividend policy, the profitability of a positive effect on dividend policy, the company's value weakens the negative influence of IOS on dividend policy, the value of the company is not able to weaken the influence of negative leverage on the dividend policy, the value of the company strengthens the influence positive profitability in dividend policy.
Keywords: Dividend Policy, Corporate Values, Investment Opportunity Set (IOS), Leverage, Profitability